PEMIKIRAN PROF. DR. ZAKIAH DARADJAT TENTANG PENDIDIKAN ISLAM BAGI REMAJA - Hamida Olfah (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Adolescence is a period when a child experiences the most rapid growth. Because it is during adolescence that there is a transition from childhood to adulthood. Every human being will experience certain phases in his life. From infancy after birth, then developing into teenagers and adults then old age. In adolescence, generally there are various kinds of changes, both physically, biologically, mentally and emotionally as well as psychosocial. The changes that occur during adolescence can affect personal life, family environment and society. Adolescents are part of society who are most vulnerable in facing temptations and pressure from their social environment. Therefore, in this period of adolescence requires special and serious attention, not only parents, but also the attention of teachers and society.